Du travail des « collectifs » à de nouvelles modalités de formation professionnelle : l'histoire du GAP - Christine Félix (Université de Provence, 2014)
This contribution seeks to take account of the genesis of a working group, the foundations of its collaboration with researchers as part of a research team in ERGAPE (ERGonomie de l'Activité des Professionnels de l'Education / Ergonomics of the activity of educational professionals) and the history of its activity in relation to training. Produced after the fact by the researcher, this account is the reconstruction of the past: a "research environment associated with a work environment" (Oddone, Ré & Briante, 1981) in which experienced teachers, trained in the tools for analysing the activity were, from 2006, led to accompany teaching teams in the implementation of educational policies and play a role in training for the teaching profession. However, can we switch from the teaching profession to that of trainer without being a trainer by profession? How can the experience of experienced teachers benefit a teaching profession training system? Under what conditions can a working group be formed as a potential resource to work with others and contribute to developing on-the-job skills?